Prevalence and Correlations of Gastrointestinal Symptoms With Endoscopic and Histologic Mucosal Healing in Crohn's Disease. (23rd April 2023) - Tse, Chung Sang; Singh, Siddharth; Valasek, Mark A.; Neill, Jennifer; Le, Helen; Collins, Angelina E.; Boland, Brigid Sweeney
Abstract : To characterize the associations between clinical disease activity with endoscopic and histologic (endohistologic) mucosal healing in Crohn's disease, we performed a secondary analysis of prospectively collected data on 424 ileocolonoscopies from 258 unique adults at a tertiary referral center from 2014 to 2021. One-third of patients (34%, 25/73) in endoscopic-histologic remission reported gastrointestinal symptoms. The 2-item patient-reported outcome measure for abdominal pain and stool frequency correlated weakly with endoscopic (Simple Endoscopic Score for Crohn's Disease; r = 0.17, 95% CI 0.08–0.26, P = 0.0003) and histologic disease activity (Global Histologic Disease Activity Score; r = 0.14, 95% CI 0.03–0.24, P = 0.015). Overall, gastrointestinal symptoms correlate poorly with endohistologic disease activity.